Dietary fiber and carboydrate contents of gathotan and gathot as functional food for people with diabetes mellitus - Puspita Mardika Sari; Desty Ervira Puspaningtyas; Rio Jati Kusuma (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2017)
Background : Gathotan and gathot are Indonesian cassava traditional fermented food from Gunungkidul, Yogyakarta. These fermented foods may be considered as an important component of a functional-foods based diet for management of type 2 diabetes mellitus (DM). Previous study found that gathotan and gathot hadve low glycemic index (GI). Fermentation processed using fungi and bacteria hadve potency to give many beneficial effects, such as prebiotic that gives contribution on the forming of short chain fatty acid (SCFA). SCFA gives many beneficial effects on metabolism and prognosis on DM type 2. However, there have been no study on the potency of gathotan and gathot as dietary fiber sources.Objectives: This study was designed to examine carbohydrate and dietary fiber content in gathotan and gathot as functional food for people with DM.Methods: Gathotan was made by spontaneous fermentation. Gathot was made by soaking overnight of gathotan, then steaming and drying. Carbohydrates content was calculated by using “carbohydrate by diference” method. Dietary fiber content was analyzed by using enzymatic gravimetri method.Results: The highest carbohydrate content was found in cassava (81,13%), followed by gathotan (68,32%), and gathot (39,03%), respectively. The highest dietary fiber content was found in gathot (17,36%), followed by gathotan (14%), and cassava (8,61%) respectively.Conclusions: Fermentation process of cassava to be gathotan and gathot are potential to increase dietary fiber and decrease carbohydrate content. KEYWORDS: gathotan, gathot, functional food, diabetes mellitus.